Survey of Clinical and Anatomic Pathology Laboratory Infrastructure in Mozambique. Issue 5 (3rd May 2021) - Ismail, Mamudo R; Noormahomed, Emília V; Lawicki, Shaun; Eichbaum, Quentin
Abstract: Objectives: Pathology services are limited in most areas of sub-Saharan Africa. This study's aim was to survey anatomic and clinical pathology services and laboratory infrastructure in Mozambique. Methods: A survey was conducted from October-December 2018 across the four central hospitals of Mozambique to determine infrastructure and pathology services available. Results: Most laboratory/pathology services in Mozambique are limited to the four central hospitals. Only 14 pathologists practice in the country despite a population of 29.5 million for the world's fifth worst workforce/population ratio. Approximately 35, 000 anatomic pathology specimens are evaluated annually. Standard services across chemistry, hematology, microbiology, and blood bank are available at the four central hospitals. Esoteric laboratory testing and immunohistochemistry are generally only available in Maputo. Conclusions: While most pathology services are available in Mozambique, many are available only at the Maputo laboratory. Expansion of pathology services and infrastructure will improve provision of effective and efficient health care as access to timely and accurate clinical diagnoses increases in Mozambique.